Comparison of the quantification of a therapeutic protein using nominal and accurate mass MS/MS. (March 2012) - Plumb, Robert S; Fujimoto, Gordon; Mather, Joanne; Potts, Warren B; Rainville, Paul D; Ellor, Nicholas J; Evans, Christopher; Kehler, Jonathan R; Szapacs, Matthew E
Background: The quantification of proteins and peptides in in vivo samples is a critical part of supporting the drug development process for biotherapeutics. LC–MS/MS using tandem quadrupole mass spectrometers is well established as the technology of choice for the quantification of small-molecule drugs and their metabolites in biological fluid. The application of accurate mass MS for quantification in a DMPK environment has attracted considerable interest in recent years.Materials & Methods: In this article we describe and compare the application of LC–high-resolution MS and LC–selected reaction monitoring (SRM) for the quantification of a therapeutics proteins.Results: The accurate mass instrumentation showed acceptable linearity and sensitivity to quantify the protein therapeutic to the level of 10 ng/ml. The accurate mass instrument was operated in accurate mass SRM using high resolution (SRM-HR), the assay was demonstrated to be linear over three orders of magnitude. By narrowing the mass window from 100 mDa to 40 mDa and then to 20 mDa the assay specificity was significantly improved, hence increasing the S/N and improving the assay sensitivity.Conclusion: The high-resolution instrument was demonstrated to be reproducible over the course of the assay. The accurate mass method sensitivity was determined to be within one order of magnitude of that obtained with a tandem quadrupole MS/MS assay.